Toward smallholder bamboo-integrated agro-silvopastoral systems in sub-Saharan Africa: assessing the impact of bamboo leaves on consumption pattern, growth performance and manure characteristics of West African dwarf goats - Sasu, Prince; Attoh-Kotoku, Victoria; Anim-Jnr, Antoinette S.; Kwaku, Michael; Adjei-Mensah, Benjamin; Adjei, Obed; Mintah, Frank Kweku (Frontiers in Animal Science, 2023)
Introduction The selection of appropriate plant species, particularly those tailored to supplement ruminants raised under agrosilvopastoral systems, remains a persistent challenge. Objective In a 30-day study, the feed intake, growth performance, and manure characteristics of West African dwarf (WAD) goats fed bamboo leaf supplement were evaluated. Materials and methods A total of 30 animals with an average weight of 9.9 ± 0.21 kg were divided into a control group, and four bamboo-supplemented groups, following a 2 x 2 factorial arrangement within a completely randomized design. Each group had six animal replicates and received the following dietary treatments: T1 (control) – 400g of basal diet composed of 60% Megathyrsus maximus and 40% Bridelia ferruginea leaves per day; T2—basal diet composed of the T1 diet supplemented with 400 g of Oxytenanthera abyssinica (A. Rich.) Munro leaves per day; T3—basal diet composed of the T1 diet supplemented with 400 g of Bambusa balcooa (Beema) leaves per day; T4—basal diet composed of the T1 diet supplemented with 600 g of O. abyssinica (A. Rich.) leaves per day; and T5—basal diet composed of the T1 diet supplemented with 600 g of B. balcooa leaves per day. The data were analyzed using generalized linear model procedures in Minitab Statistical Software at a 5% significance level. Results The results showed varied (p < 0.05) dry matter compositions spanning from 894.3 to 910 g/kg with the highest contents of crude protein (194 g/kg), nitrogen (31 g/kg), crude fibre (302 g/kg), ash (156 g/kg), acid detergent fibre (429 g/kg), and acid detergent lignin (3.6 g/kg) recorded for B. ferruginea. The leaves of Bambusa balcooa contained the highest neutral detergent fibre (481 g/kg) while M. maximus had the highest organic matter content (911 g/kg). Significant interaction effect (p < 0.05) was observed between the supplement type and the supplementation level, impacting various parameters including feed intake ranging from 398 g (T1) to 469 g (T3) per day, weight gain from 27 g (T1) to 72 g (T2) per day, feed conversion efficiency from 6% (T1) to 15% (T2), manure output from 241 g (T2) to 260 g (T5) per day, carbon- nitrogen (C: N) ratio from 9 (T2) to 20 (T5), faecal acidity levels from 4 (T1) to 5 (T4). Comparatively, higher daily dry matter intake was recorded for the animal groups fed the B. balcooa supplement than their counterparts fed the O. abyssinica supplement. However, the O. abyssinica supplemented groups were more efficient in converting feed to body weight, with feed conversion efficiency approximately 9% higher than the B. balcooa-supplemented groups. Furthermore, in general, the animal groups that received a daily supplement of 400 g gave higher feed efficiency, with performance approximately 3.2% higher compared to the groups receiving 600 g. Likewise, these groups displayed higher faecal N output while concurrently achieving a reduced C: N ratio, indicative of enhanced nutrient utilization and potential environmental benefits. Conclusion To conclude, integrating 400 grams of bamboo leaves into animal diet can enhance basal diet consumption, accelerate animal growth, and yield manure akin to chemical fertilizers, making it a valuable strategy for bamboo-integrated agro-silvopastoral systems practitioners.